2014
DOI: 10.1080/10691898.2014.11889692
|View full text |Cite
|
Sign up to set email alerts
|

Teaching an Application of Bayes' Rule for Legal Decision-Making: Measuring the Strength of Evidence

Abstract: Although Bayesian methodology has become a powerful approach for describing uncertainty, it has largely been avoided in undergraduate statistics education. Here we demonstrate that one can present Bayes' Rule in the classroom through a hypothetical, yet realistic, legal scenario designed to spur the interests of students in introductory-and intermediate-level statistics classes. The teaching scenario described in this paper not only illustrates the practical application of Bayes' Rule to legal decision-making,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…For this reason, appropriately processing important information in a situation, such as a medical diagnosis test, is a crucial competence of professionals as well as laymen when confronted with epistemic uncertainty (e.g., Koller and Hoffrage, 2015). Similar judgments and decisions are also essential for lawyers, if evidence is given concerning a person being guilty or innocent (e.g., Satake and Murray, 2014), as well as in other professions (Hoffrage et al., 2015; Mellers et al., 2017). By contrast, a failure of processing information in a situation of epistemic uncertainty can lead to misjudgments and severe consequences (e.g., Stine, 1998; Schneps and Colmez, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, appropriately processing important information in a situation, such as a medical diagnosis test, is a crucial competence of professionals as well as laymen when confronted with epistemic uncertainty (e.g., Koller and Hoffrage, 2015). Similar judgments and decisions are also essential for lawyers, if evidence is given concerning a person being guilty or innocent (e.g., Satake and Murray, 2014), as well as in other professions (Hoffrage et al., 2015; Mellers et al., 2017). By contrast, a failure of processing information in a situation of epistemic uncertainty can lead to misjudgments and severe consequences (e.g., Stine, 1998; Schneps and Colmez, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To understand the basic concept in Bayesian analysis, one could start with a historical overview of Bayes theorem. Satake and Murray (2014) have developed interesting methods for teaching Bayes theorem using a legal scenario. Next, the different approaches to calculating/estimating posterior distributions could be presented (e.g., grid estimation, quadratic estimation, and MCMC).…”
Section: Alternative Contentmentioning
confidence: 99%
“…One reason for the importance of Bayes' rule is that it allows an update to probability on the basis of new evidence for decision making [3]. This decision making in so-called Bayesian situations (i.e., situations in which Bayes' rule can be applied) is decisive in various non-mathematical disciplines such as medicine [4], law [5] and economics [6]. However, research in psychology found consistently, over several decades, that people struggle greatly when dealing with Bayesian situations [7][8][9].…”
Section: Introductionmentioning
confidence: 99%